Pengaruh pemberian gel ekstrak daun ekor naga (Rhaphidophora pinnata) terhadap diferensial leukosit tikus yang diinduksi carrageenan air pouch - Kasmadi, Fathnur Sani; Rahman , Ave Olivia; Rahman, Havizur (Journal of Pharmaceutical and Sciences, 2023)
Ekor naga leaves gel preparations have been pharmacologically proven to have an anti-inflammatory effect by reducing inflammation in the skin of mice. Leukocyte differential describes the repair of leukocyte cells in overcoming inflammation. The research aimed to determine the effect of administering ekor naga leaves extract gel on the differential number of leukocytes in mice induced by air pouch carrageenan. The research method used is experimental design. The treatment group consisted of 5 groups, with five mice in each group. Positive control group (Hydrocortisone®), Formula 0 (Gel Base), Formula 1 (Extract concentration 10%), Formula 2 (Extract concentration 15%), Formula 3 (Extract concentration 20%). The research data obtained was analyzed using one-way ANOVA with a confidence level of 95%. Research results show that Formula 2 is the best.